Strategi Ekonomi Berbasis Relasi Sosial pada Suku Jawa: Studi Tujuh Pedagang Sari Laut di Kota Berau Kalimantan Timur - Risnaeni; St. Junaeda (Jurnal Ekonomi dan Riset Pembangunan, 2023)
This study aims to determine: the relationship between Javanese traders who trade on Jalan Pangeran Antasari, Berau City and the efforts made by Sari Laut traders to maintain their business amidst competition for more modern food stalls. This type of research is descriptive in nature with a qualitative approach. The process of collecting data through, from: documentation, observation, and interviews. In this study, seven individual traders of Sari Laut were involved. The results showed that the relationship between fellow Javanese Sari Laut traders formed a positive social network between traders so as to form a kinship bond. Then high enthusiasm and hard work, providing good service for buyers or customers, paying attention to the taste of the dishes they serve, keeping their place clean and involving the family to help trade. In addition, maintain the human resources that the brand has and establish good relations between fellow traders and the surrounding community.